Laboratory study of water absorption of modified mortar - Borhan, M.M (Universiti Malaysia Sarawak, (UNIMAS), 2011)
This study investigates the effects of polymer additives namely polyvinyl acetate (PVAc) on water absorption and compressive strength of mortar. Twelve mortar mixtures were investigated for water absorption test and compressive strength test.